Kewirausahaan Sosial Melalui Budidaya Tanaman Hydroponic Bagi Warga Pamulang Hill 3 Tahap 2, Rawakalong, Gunung Sindur, Bogor - Tohirin, Tohirin; Wijiharjono, Nuryadi (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2020)
Soil is no longer the primary medium for economical environmental initiatives. Urban gardening is a technique that uses hydroponics. Hydroponic plant cultivation can have an environmental and economic impact if taken seriously. According to the scenario study, housewives dominate in Pamulang Hill 3 Phase 2, Rawakalong, Gunung Sindur, and Bogor. They have enough time to do things that can generate additional income. This program aims to teach the women how to use the hydroponic system to grow gardens or vegetables. In hydroponic farming, the nutritional needs of plants are met by using water or nutrient-rich mineral solutions instead of soil. Urban locations with limited land can benefit greatly from this hydroponic farming technique. The long-term effect of this service is higher income and well-being